1995
DOI: 10.1111/j.1475-097x.1995.tb00430.x
|View full text |Cite
|
Sign up to set email alerts
|

99mTc‐MAG3 kinetics in the normal pig. A comparison to 131I‐OIH and 125I‐iothalamate after single injection and during continuous infusion

Abstract: An invasive comparative study of some pharmacokinetic aspects of 99mTcmercaptoacetyltriglycine (MAG& 1311-orthoiodohippurate (OIH), and 1251-iothalamate (iothalamate) was performed in six pigs 0-150 min after a simultaneous single injection (SI) and during a subsequent 90 rnin of continuous infusion ((21). The total plasma clearance and the renal clearance of MAG3 were about 75% that of OIH. The renal clearance of MAG3 was about 2% times the glomerular filtration rate. The distribution volume of MAG3 was 71% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Renal E for Tc-99m-MAG3 has been found to vary in experimental animals between 54% in pigs [5] and >80% in rodents [6,7]. E in humans, measured from renal vein catheterisation in five patients, was reported to be 55% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Renal E for Tc-99m-MAG3 has been found to vary in experimental animals between 54% in pigs [5] and >80% in rodents [6,7]. E in humans, measured from renal vein catheterisation in five patients, was reported to be 55% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Urographic contrast media such as iopamidol and 99m Tc‐MAG3 are primarily filtered through the glomerulus and primarily not reabsorbed or secreted in the renal tubule, 6,45 therefore, it is possible to monitor their transit through vascular and tubular compartments through DCE‐CT, MRI and renal scintigraphy. The resulting contrast kinetics provides a measure of renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that 99m Tc‐MAG 3 and 123 I‐OIH share characteristics of renal uptake and elimination, even in patients with impaired renal function (Bubeck et al, 1990; Rehling et al, 1995; Russell & Dubovsky, 1999; Russell et al, 1988), whereas others indicate that 99m Tc‐MAG 3 has a larger protein binding, slower plasma Cl, larger extraction efficiency in the tubules and a higher excretion through the bile than 123 I‐OIH (Bubeck et al, 1990; Rehling et al, 1995). A review by Itoh et al stated that the plasma Cl ratio of 99m Tc‐MAG 3 / 123 I‐OIH was 0.44–1.07, and protein binding for 99m Tc‐MAG 3 was higher (75–90%) compared to that of 123 I‐OIH (53–74%) (Itoh, 2001).…”
Section: Discussionmentioning
confidence: 99%